Factors Influencing Continuance Intention of Complaint Service: A Case Study of QLUE - Ardiati Utami Sarjono; Atalya Yoseba S.; M. Aulia Hafidh; Rosa Nur Rizky FT; Syafiq Abdillah U.; Achmad Nizar Hidayanto (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2022)
The quality of information systems is the key to user satisfaction with an information system application. As a theoretical basis, this study uses the Information System Success Model to discuss the influence of the quality of information systems on the continued use of Information Systems applications. Qlue is used as a case study as one of the complaint service applications. This study uses a questionnaire with 299 data collected using Google Forms which are distributed through various social media. Then to test the hypothesis, we processed the data by Partial Least Square (PLS) using SmartPLS application. This study explains that the factors that influence the intention to continue using Qlue are satisfaction with system quality and information quality, including aesthetic design, immediacy, and customization.